The effect of design and construction practises [i.e. practices] on the premature cracking performance of asphalt pavements - Malan, G. W.(Gerhard Wilhelm) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Eng. (Civil)) -- University of Stellenbosch, 1991.